2018
DOI: 10.1177/1076029618774145
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Coagulation Effect Achieved by OctaplasLG Versus Fresh Frozen Plasma in Pediatric Cardiac Surgical Patients

Abstract: OctaplasLG is indicated for use in patients undergoing cardiac surgery who require replacement of multiple clotting factors. The use of OctaplasLG over single-donor fresh frozen plasma (FFP) may have beneficial effects when considering the transmission of enveloped viruses. Additionally, it has the potential for fewer adverse reactions, reduced disease transmission, and a more homogenous coagulation factor composition. However, its efficacy and safety have not yet been evaluated in the pediatric population. Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Immediately after surgery, INR and aPTT were significantly lower in patients who received octaplas than in those who received FFP, and the proportion of patients who received additional plasma transfusions was significantly higher in the FFP group compared with the octaplas group. Furthermore, the rate of postoperative infections requiring the use of antibiotics was significantly higher in the FFP group compared with the octaplas group, and no transfusion reactions were observed in either group (18). In a secondary analysis of a prospective, observational study that included 443 critically ill children who received plasma transfusions, FFP and SDP were associated with similar reductions in INR (p = 0.80).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Immediately after surgery, INR and aPTT were significantly lower in patients who received octaplas than in those who received FFP, and the proportion of patients who received additional plasma transfusions was significantly higher in the FFP group compared with the octaplas group. Furthermore, the rate of postoperative infections requiring the use of antibiotics was significantly higher in the FFP group compared with the octaplas group, and no transfusion reactions were observed in either group (18). In a secondary analysis of a prospective, observational study that included 443 critically ill children who received plasma transfusions, FFP and SDP were associated with similar reductions in INR (p = 0.80).…”
Section: Discussionmentioning
confidence: 87%
“…Octaplas was compared with FFP in a retrospective analysis that included 105 pediatric patients aged <2 years who were undergoing tetralogy of Fallot repair (18). Most patients received octaplas and FFP transfusions in the operating room after cardiopulmonary bypass (93.8 and 85.0%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…4 A retrospective study investigated paediatric cardiac surgical patients that were aged below 2 years and less than 10 kg (undergoing complete tetralogy of Fallot repair), that received either FFP or SD plasma (OctaplasLG) during surgery. 7 The study included 105 patients over a 10-year period, of which 5 years of FFP use and 5 years of SD plasma use. The study showed that SD plasma was as effective in achieving haemostasis as FFP.…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that SD plasma was as effective in achieving haemostasis as FFP. 7 In a recently published phase IV study in which the safety, tolerability and efficacy of SD plasma (Octaplas) was investigated, 50 patients aged <16 years were included, of which 37 were 0-2 years old. 5 No hyperfibrinolytic or thromboembolic events or adverse drug reactions were reported after transfusion of SD plasma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation